MODEL PEMBELAJARAN KOOPERATIF TIPE SCRAMBLE BERBANTU FLASH CARD SISWA KELAS II SDN 04 KOTO BARU - Ayu Ningsih Almirus; Rusdi Indra Hasibuan; Maisita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low beginning reading ability of second-grade students at SDN 04 Koto Baru. This condition was indicated by the large number of students who experienced difficulties in recognizing words, reading simple sentences, and actively participating in Indonesian language learning activities. One of the efforts that can be made to overcome these problems is by implementing the Scramble type cooperative learning model assisted by Flash Card media, which is able to create an active, interesting, and enjoyable learning atmosphere. This study aimed to determine the effect of the Scramble type cooperative learning model assisted by Flash Cards on the beginning reading ability of second-grade students at SDN 04 Koto Baru. This research employed a quantitative approach with an experimental research type using a Pre-Experimental Design in the form of a One Group Pretest-Posttest Design. The population as well as the sample of this study consisted of all second-grade students at SDN 04 Koto Baru, totaling 17 students. Data were collected through tests, questionnaires, and observations. Data analysis was conducted through normality testing and hypothesis testing using appropriate statistical tests. The results of the study are expected to show that the implementation of the Scramble type cooperative learning model assisted by Flash Cards has a positive effect on students' beginning reading ability. This learning model can improve students' activeness, motivation, and ability to recognize letters, read words, and understand simple sentences in Indonesian language learnin)